Highly In‐Plane Anisotropic 2D PdSe2 for Polarized Photodetection with Orientation Selectivity. (7th October 2020) - Pi, Lejing; Hu, Chunguang; Shen, Wanfu; Li, Liang; Luo, Peng; Hu, Xiaozong; Chen, Ping; Li, Dongyan; Li, Zexin; Zhou, Xing; Zhai, Tianyou
Abstract: Polarized photodetection based on anisotropic two‐dimensional materials display promising prospects for practical application in optical communication and optoelectronic fields. However, most of the reported polarized photodetection are limited by the lack of valid tunable strategy and low linear dichroism ratio. A peculiar noble metal dichalcogenide—PdSe2 with a puckered pentagonal structure and abnormal linear dichroism conversion—potentially removes these restrictions and is demonstrated in this study. Herein, azimuth‐dependent reflectance difference microscopy combined with anisotropic electrical transport measurements indicate strong in‐plane anisotropic optical and electrical properties of two‐dimensional PdSe2 . Remarkably, the typical polarization‐resolved photodetection exhibits anisotropic photodetection characteristics with a dichroic ratio up to ≈1.8 at 532 nm and ≈2.2 at 369 nm, and their dominant polarization orientation differs by 90° corresponding to the a ‐axis and b ‐axis, respectively. The unique orientation selection behavior in polarization‐dependent photodetection can be attributed to the intrinsic linear dichroism conversion. The results make 2D PdSe2 a promising platform for investigating anisotropic structure–property correlations and integrated optical applications for novel polarization‐sensitive photodetection. Abstract : Strong intrinsic anisotropy and unique orientation selectivity behavior with highly‐sensitive polarized photodetection of 2D PdSe2 is demonstrated. The polarization‐resolved photodetection exhibits a strong anisotropic photodetection behavior with a dichroic ratio up to ≈1.8 at 532 nm and ≈2.2 at 369 nm, and the dominant polarization orientation differs by 90° corresponding to the a‐axis and b‐axis, respectively.